Impact of COVID-19 epidemic on Lombardy's prisons (Italy): transmission and measure of prevention. (20th October 2021) - Mazzilli, S; Giuliani, R; Arzilli, G; Cairone, C; Sebastiani, T; Scardina, G; Cocca, G; Tavoschi, L; Ranieri, R
Abstract: Background: Early on in the COVID-19 pandemic, scientific community highlighted the potential risk of epidemics occurring inside prisons. Consequently, specific operational guidelines were promptly released and stringent containment measures quickly implemented, including access restriction to essential staff only. During the 2nd epidemic wave prevention strategies were gradually relaxed, visitors were readmitted and people in prison (PiP) activities were repristinated. Here, we describe the spread of COVID-19 in 18 detention facilities in Lombardy region, Italy, during the 1st(Mar-Jul 2020) and 2nd(Oct 2020-Feb 2021) waves and the impact of prevention and control measures implemented in prison. Methods: We conducted a descriptive retrospective analysis of cases' distribution. Moreover, a comparison among the epidemic burden affecting POs and PiP and a correlation analysis between the number of cases occurred and prevention measures implemented were carried out. Results: Our population consists of a monthly average of 2269 prison officers (POs) and 7604 PiP. POs were at higher risk of contracting COVID-19 during both waves. Occurrence of cases among PiP was temporally associated with cases among POs. There was heterogeneity in the size of outbreaks across different prison facilities. During the second wave, COVID-19 spread more widely in prison both among POs (2ndwave attack rate (AR) per 1000 individuals: 27.2; monthly range (MR): 0.9-64.5 vs 1stwave AR 2.4; MR: 0.0-12.1) and PiP (2ndwave AR: 23.5; MR: 11.6-50.8 vs 1stwave AR 1.6; MR: 0-5.2). Conclusions: Prevention and control measures adopted timely during the first wave were effective to limit Sars-CoV-2 spread within prison facilities. According to our findings, POs and PiP are population groups at high risk for acquiring and transmitting COVID-19 and should be prioritized for testing, active case finding and vaccination. This study highlights the importance of including prison settings within emergency preparedness plans. Key messages: Stringent prevention and control measures when adopted timely were effective to protect detention facilities from Sars-CoV-2 spread. Our study, reporting the burden of COVID-19 epidemic experienced by prison of Lombardy, Italy, highlights the importance of including prison settings within emergency preparedness plans.